Spatial‐temporal variations of evapotranspiration and runoff/precipitation ratios responding to the changing climate in the Pacific Northwest during 1921‐2006. Issue 2 (25th January 2013) - Liu, Mingliang; Adam, Jennifer C.; Hamlet, Alan F.
Abstract : [1] Water resources in the Pacific Northwest (PNW) are very sensitive to climate change. There are still big knowledge gaps on how evapotranspiration (ET) varies in responding to changing temperature (T) and precipitation (P) over different zones in terms of supply and demand regime for ET. Here, we employ the Variable Infiltration Capacity (VIC) hydrologic model and a high‐resolution meteorological data set to quantify spatial and seasonal variations of ET and the runoff (R)/precipitation (P) ratio over the PNW and attribute effects of T and P. We evaluate modeled ET and R with eddy covariance measurements, upscaled regional ET, and reconstructed natural streamflow. Simulation results indicate that water‐limited (annual potential ET (PET) ≥ P) and energy‐limited zones (annual PET < P) have different responses to changing climate. In general, water‐limited zones tend to be more associated with increasing ET and decreasing R/P than do energy‐limited regions. With controlled simulation experiments, we document that trends in annual and warm‐season ET and R/P are dominantly controlled by P, while in the cool season they are mainly controlled by T. During an entire cycle of the Pacific Decadal Oscillation (1947‐2006), the PNW experienced a substantial increase in ET and a decrease in R and R/P under the trends of warming and drying. In this snowmelt‐dominated region where warming‐induced changes to the snowpack are impacting seasonal freshwater availability, decreases in R/P could further aggravate water scarcity. To reduce uncertainties, high‐resolution meteorological data sets and intensive model calibrations and evaluations against ET are required. Key Points: Modeled ET and R are evaluated with site and regional observations Water‐ and energy‐limited zones has different responses to changing climate There are significant seasonal and spatial variations in ET and R/P